Financial Distress, Sales Growth, Profitabilitas dan Penghindaran Pajak - Ningsih, Ida Ayu Made Widya; Noviari, Naniek (E-Jurnal Akuntansi; Vol 32 No 1 (2022)DO - 10.24843/EJA.2022.v32.i01.p17, 2022)
This study aims to determine the effect of financial distress, sales growth, and profitability on tax avoidance. This research was conducted in a manufacturing company listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period with a total of 182 companies. The sample used is 80 companies with a total sample of 240 observations in three years. The analytical technique used in this research is multiple linear regression analysis. The test results in this study found that financial distress has a positive and significant effect on tax avoidance, sales growth has a positive and significant effect on tax avoidance, and profitability has a positive and significant effect on tax avoidance. Keywords: Financial Distress; Sales Growth; Profitability; Tax Avoidance.